2013
DOI: 10.1177/0022002713492649
|View full text |Cite
|
Sign up to set email alerts
|

Fair-Weather Allies? Terrorism and the Allocation of US Foreign Aid

Abstract: While it is commonly assumed that the United States uses foreign aid as an instrument to combat global terrorism, it is unclear whether it views terrorist threats to other countries, particularly its allies, with urgency. We show that the relationship between transnational terrorism and foreign aid flows is strongly conditional on whether terrorist activity based in a potential recipient directly threatens the United States. Using data on terrorist attacks and casualties in potential recipient countries, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 48 publications
(52 reference statements)
2
55
0
Order By: Relevance
“…This finding is consistent with our theoretical underpinnings from Boutton and Carter (2013) because donors have been documented to allocate more aid towards fighting transnational terrorist activities in recipient countries because they are more likely to target their interests. Moreover, the propensity of donor interest at stake is likely to increase with initial levels of transnational terrorism, such that the effect of foreign aid is most significant in recipient countries with the highest levels of transnational terrorism.…”
Section: Further Discussion Of Results and Policy Implicationssupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is consistent with our theoretical underpinnings from Boutton and Carter (2013) because donors have been documented to allocate more aid towards fighting transnational terrorist activities in recipient countries because they are more likely to target their interests. Moreover, the propensity of donor interest at stake is likely to increase with initial levels of transnational terrorism, such that the effect of foreign aid is most significant in recipient countries with the highest levels of transnational terrorism.…”
Section: Further Discussion Of Results and Policy Implicationssupporting
confidence: 90%
“…We have consistently established that foreign aid (bilateral, multilateral and total) is effective at fighting terrorism exclusively in countries where existing levels of transnational terrorism are highest. This finding is consistent with our theoretical underpinnings from Boutton and Carter (2013) because donors have been documented to allocate more aid towards fighting transnational terrorist activities in recipient countries because they are more likely to target their interests.…”
Section: Conclusion and Further Directionssupporting
confidence: 90%
“…Moreover, these recipients can further play-up the terrorism threat in order to receive more aid. Button and Carter (2014) have shown that the nexus between foreign aid and transnational terrorism is contingent on whether terrorist activity in the recipient country threatens the United States directly or not. Hence, the United States is more likely to offer aid to countries in which terrorist activities target her interests.…”
Section: Literature Reviewmentioning
confidence: 99%
“…44. Boutton and Carter 2014. 14 International Organization This approach has important advantages. We use aid commitments to predict disbursements, so our variables can be interpreted as discretionary deviations by the executive branch from appropriated aid levels.…”
Section: Dependent Variablesmentioning
confidence: 99%